Mindfulness and Art Therapy Drawing: Innovative Therapy to Reduce Student Stress - Triwijayanti, Renny; Rahmania, Annisa; Husna, Hani Patul (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Academic stress is a condition of pressure experienced by individuals due to demands in higher education. This study aimed to examine the effectiveness of mindfulness and art therapy drawing in reducing stress among final-year students. The study employed a pre-experimental one group pretest-posttest design. A total of 41 students received the intervention after completing a pretest, followed by a posttest. Analysis showed that the mean stress score before intervention was 148.22 and decreased to 125.88 after intervention. The Paired T-Test yielded a p-value of 0.001 (≤ 0.05), indicating a significant effect of the intervention on stress reduction. Mindfulness therapy helps individuals reinterpret stress more positively, while art therapy drawing serves as a creative outlet for emotional expression. The combination of both proved effective in reducing student stress levels.